Coassembly of nucleus-targeting gold nanoclusters with CRISPR/Cas9 for simultaneous bioimaging and therapeutic genome editing. Issue 1 (21st November 2020) - Tao, Yu; Yi, Ke; Hu, Hanze; Shao, Dan; Li, Mingqiang
Abstract : Protamine–gold nanoclusters were developed as nanocarriers for CRISPR/Cas9 delivery to achieve efficient genome editing and bioimaging. Abstract : The clustered regularly interspaced short palindromic repeats (CRISPR)/associated protein 9 (CRISPR/Cas9) technology enables genome editing with high precision and versatility and has been widely utilized to combat viruses, bacteria, cancers, and genetic diseases. Nonviral nanocarriers can overcome several limitations of viral vehicles, including immunogenicity, inflammation, carcinogenicity, and low versatility, and thus represent promising platforms for CRISPR/Cas9 delivery. Herein, we for the first time develop the application of protamine-capped gold nanoclusters (protamine–AuNCs) as an effective nanocarrier for Cas9–sgRNA plasmid transport and release to achieve efficient genome editing. The protamine–AuNCs integrate the merits of AuNCs and protamine: AuNCs are able to promptly assemble with Cas9–sgRNA plasmids to allow efficient cellular delivery, while the cationic protamine facilitates the effective release of Cas9–sgRNA plasmids into the cellular nucleus. The AuNCs/Cas9–gRNA plasmid nanocomplexes can not only achieve successful gene editing in cells but also knock out the oncogenic gene for cancer therapy. Moreover, the AuNCs with excellent photoluminescence characteristics endow our nanoplatform with the functionality of bioimaging. Overall, our study provides strong evidence that demonstrates protamine–AuNCs as an effective CRISPR/Cas9 delivery tool for gene therapy.